An Analysis of Hadith Teaching Methods in Muhammad Abdul Qadir Ahmad’s Turuqu Ta’limi at-Tarbiyyah al-Islamiyyah: A Content Study - Khoirotus Sa'diyah; Basuki Basuki (Abjadia : International Journal of Education, 2026)
The teaching method is a way of delivering lesson material, so that the material is easy to understand and well known by students. Of course, in selecting the material used, teachers must be really careful and understand which method can be used according to the character of the students, conditions and atmosphere in the classroom. This study will explain the method of teaching hadith in the book Turuqu Ta’limi at-Tarbiyyah al-Islamiyyah by Abdullah bin Ahmad. The main source in this study is the book Turuqu Ta’limi at-Tarbiyyah al-Islamiyyah by Muhammad Abdul Qadir Ahmad. The researcher used the literature study research method. While the supporting sources are articles from previous research findings related to it. With the content analysis data analysis technique, this study has Three core components were identified: (1) conceptualization of hadith, (2) pedagogical purposes, and (3) methodological strategies such as memorization, discussion, and contextualization. This article is also available at gb777